2007
DOI: 10.1038/nnano.2007.388
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanical analysis of cells from cancer patients

Abstract: We propose and demonstrate a purely optical approach to trap and align particles using the interaction of polarized light with periodic nanostructures to generate enhanced trapping force. With a weakly focused laser beam, we observed efficient trapping and transportation of polystyrene beads with sizes ranging from 10 µm down to 190 nm as well as cancer cell nuclei. In addition, alignment of non-spherical dielectric particles to a 1-D periodic nanostructure was achieved with low laser intensity without attachm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

61
1,289
2
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,691 publications
(1,409 citation statements)
references
References 30 publications
61
1,289
2
11
Order By: Relevance
“…Cell mechanical properties play an important role in critical cellular functions, including migration, division and shape [11]. Studies into the mechanics of single cells have implicated that cell mechanics are closely related to human health and disease [12,13]. Any deviations in the mechanical properties of cells may affect the physiological functions and give rise to disease, while disease can also result in mechanical properties changes in living cells [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell mechanical properties play an important role in critical cellular functions, including migration, division and shape [11]. Studies into the mechanics of single cells have implicated that cell mechanics are closely related to human health and disease [12,13]. Any deviations in the mechanical properties of cells may affect the physiological functions and give rise to disease, while disease can also result in mechanical properties changes in living cells [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, the atomic force microscopy (AFM) has been proven to be a powerful, versatile and easy-to-use tool for investigating the mechanical properties of single cells [13][14][15][16][17][18][19][20][21][22][23]. First, AFM can work in fluids and this enables the researchers to perform the experiments on living cells in situ.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, cell deformability can be used as an intrinsic marker for identifying pathological conditions. 8,19,20 For example, deformability is known to play a crucial role in the mobility of cancerous cells; 4,21 and a decrease in RBC deformability has been proven to be relevant in several human diseases (see Table 1). …”
Section: Mechanical Characterization Techniquesmentioning
confidence: 99%
“…The lack of clinical relevance is due to the very low measurement throughput and tedious operation procedures of conventional techniques for measuring the biophysical properties of cells. 4,[7][8][9] Compared to conventional techniques, the advantages of small sample volume, integration capability, biocompatibility and fast response make microfluidic technologies attractive for studying cells. Recent decades have witnessed significant advances of microfluidic technologies for biochemical characterization of cells.…”
Section: Introductionmentioning
confidence: 99%
“…Atomic force microscopy (AFM)‐based single cell stiffness study for different cancer cells including lung, breast and pancreatic, have shown that malignancy increase cell deformability at the single cell level although CTC are still more stiffer than blood cells 40. Therefore, in addition to size, the unique deformability of CTCs is also a factor that can be used for selective capture and isolation of CTCs.…”
Section: Microfluidics‐based Materials Interface For Ctcs Capturementioning
confidence: 99%